The astronaut who painted the moon : the true story of Alan Bean - Robbins, Dean, 1957- (Orchard Books, an imprint of Scholastic Inc., 2019)
"Journey to the Moon on the Apollo 12 mission with astronaut and artist Alan Bean! As a boy, Alan wanted to fly planes. As a young navy pilot, Alan wished he could paint the view from the cockpit. So he took an art class to learn patterns and forms. But no class could prepare him for the beauty of the lunar surface some 240,000 miles from Earth. In 1969, Alan became the fourth man and first artist on the moon. He took dozens of pictures, but none compared to what he saw through his artistic eyes. When he returned to Earth, he began to paint what he saw. Alan's paintings allowed humanity to experience what it truly felt like to walk on the moon."--